Penerapan Metode Kibar Dalam Peningkatan Baca Tulis Al-Qur'an Pada Siswa Di SMP Negeri 24 Medan - Mutiah, Siti (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The research of this study was to describe and critically analyze the application of the kibar method, the results, and the supporting and inhibiting factors in improving the reading and writing of the Qur'an among students at SMP Negeri 24 Medan. The research used is a qualitative case study in which the analysis technique is carried out by collecting observational data, interviews, documentation. The results of this study are that Islamic/Al-Qur'an religious teachers have implemented the fluttering method in increasing the reading and writing of the Qur'an in each class, and it has been very enthusiastically received by students. The results of the study show: (1) The process of applying the waving method is classical, namely learning the Qur'an together. The way the teacher gives examples of reading then students imitate; and private, namely listening one by one. (2) The application of the waving method in Al-Qur'an learning activities can improve students' ability to read the Qur'an. (3) The inhibiting factors in the application of the waving method include: teachers are not able to understand each child's learning characteristics, parents do not accompany learning at home, and children are not conducive and often change their feelings quickly. And the supporting factors for this waving method lie in the teacher's ability to read the book, the role of parents in accompanying children to learn to read the Koran in the family environment, children's abilities, and a conducive classroom atmosphere.